2012
DOI: 10.1371/journal.pone.0036055
|View full text |Cite
|
Sign up to set email alerts
|

ZIP8 Zinc Transporter: Indispensable Role for Both Multiple-Organ Organogenesis and Hematopoiesis In Utero

Abstract: Previously this laboratory characterized Slc39a8-encoded ZIP8 as a Zn2+/(HCO3 –)2 symporter; yet, the overall physiological importance of ZIP8 at the whole-organism level remains unclear. Herein we describe the phenotype of the hypomorphic Slc39a8(neo/neo) mouse which has retained the neomycin-resistance gene in intron 3, hence causing significantly decreased ZIP8 mRNA and protein levels in embryo, fetus, placenta, yolk sac, and several tissues of neonates. The Slc39a8(neo) allele is associated with diminished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 47 publications
5
88
0
Order By: Relevance
“…While our manuscript was under review, Gálvez-Peralta et al (52) reported the characterization of the ZIP8 hypomorphic mouse, which carries a neomycin resistance gene in intron 3 of Zip8 (Slc39a8), resulting in markedly decreased levels of ZIP8 in the embryo, yolk sac, fetus, placenta, and other tissues of neonates. ZIP8 hypomorphic mice exhibit severe anemia as embryos and neonates and do not survive more than 48 h after birth.…”
Section: Discussionmentioning
confidence: 99%
“…While our manuscript was under review, Gálvez-Peralta et al (52) reported the characterization of the ZIP8 hypomorphic mouse, which carries a neomycin resistance gene in intron 3 of Zip8 (Slc39a8), resulting in markedly decreased levels of ZIP8 in the embryo, yolk sac, fetus, placenta, and other tissues of neonates. ZIP8 hypomorphic mice exhibit severe anemia as embryos and neonates and do not survive more than 48 h after birth.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-488 has been shown to regulate ZIP8 expression during pathogenesis of osteoarthritis (381). ZIP8 plays indispensable roles in both multiple-organ organogenesis and hematopoiesis during early embryogenesis, because hypomorphic Zip8 mice show hypoplasia of multiple organs, such as the spleen, liver, kidney, and lung, and defects in hematopoiesis (118).…”
Section: H Zip8 (Liv-1 Subfamily)mentioning
confidence: 99%
“…Knockout of ZIP8 in mice causes failures in hematopoiesis and organogenesis of the spleen, liver, kidney, and lung, with associated perinatal lethality [14]. Zip8 −/− mice exhibited profound anemia and have significantly lowered amounts of iron and zinc in various tissues, with the hematopoietic defect seemingly being caused by the combination of iron and zinc deficiency.…”
Section: New Proteins Are Involved In Iron Trafficking and Utilizationmentioning
confidence: 99%